Selection of unrelated donors for allogeneic transplantation using post-transplant cyclophosphamide in acute lymphoblastic leukemia: An analysis by the Acute Leukemia Working Party of the European Society for Blood and Marrow Transplantation - Jaime Sanz; Allain-Thibeault Ferhat; Alexander Kulagin; Nicolaus Kröger; Montserrat Rovira; Lorenzo Lazzari; Mutlu Arat; Juan Montoro; Jurjen Versluis; Péter Reményi; Simona Sica; Didier Blaise; et al. (Haematologica)
Conflicting data exist on the impact of mismatched unrelated donor (MMUD) compared to matched unrelated donor (MUD) in hematopoietic cell transplantation (HCT) with post-transplant cyclophosphamide (PTCy), highlighting the need for disease-specific research. We conducted a retrospective analysis of donor characteristics in 350 patients with acute lymphoblastic leukemia (ALL) in complete remission (CR) who received 8/8 human leukocyte antigen (HLA)-matched MUD and 7/8 HLA-matched MMUD. The primary endpoint was leukemia-free survival (LFS). The median age was 37 years (range, 18-76), with 231 (66%) in first CR, and 280 (80%) diagnosed with B-cell ALL. The median donor age was 28 years (range, 18-57), with 237 (68%) MUD and 113 (32%) MMUD. The use of MUD or MMUD did not have a significant impact on LFS or other transplant outcomes. Among other donorrelated variables, CMV-negative donor for a CMV-negative recipient was associated with improved LFS (HR 0.55; 95% CI 0.32-0.96) and overall survival (HR 0.52; 95% CI 0.28-1), while older donor age showed an increased risk of acute graft-versus-host disease (GVHD) grade III-IV (HR 1.7; 95% CI 1.1-2.64) and female donor to male recipient combination increased the risk of grade II-IV acute GvHD (HR 1.78; 95% CI 1.05-3). In conclusion, non-HLA donor characteristics rather than HLA matching should be prioritized to guide unrelated donor selection for ALL patients in the PTCy HCT setting.